The Effect of Project Based Learning Implementation Toward Students’ Motivation and Learning Result at Elementary School - Mukhlis Syahroni; Parji Parji; Muhammad Hanif (Journal of Social Research, 2026)
The Merdeka Curriculum emphasizes deep learning, making Project-Based Learning (PjBL) a promising method to enhance students' motivation and learning outcomes. However, at SDN 01 Demangan, diagnostic assessment revealed that only 16.67% of sixth-grade students were in the skilled category, while 72.22% remained in the less skilled category, indicating persistent challenges in motivation and learning achievement. This study aims to analyze the effect of Project-Based Learning implementation on students' motivation and learning outcomes in the Integrated Science (IPAS) subject. Using a quantitative approach with a one-group pretest-posttest design, this research involved 18 sixth-grade students who participated in a PjBL project themed "Indonesia Global Expo," creating three-dimensional cultural envelopes. Data were collected through motivation questionnaires and learning outcome assessments covering cognitive, affective, and psychomotor aspects, then analyzed using descriptive statistics, paired sample t-tests, and Wilcoxon signed-rank tests. The findings reveal significant improvements across all measured aspects. Motivation scores increased from a mean of 82.39 to 85.44, while learning outcomes improved from 85.28 to 88.22, with a statistically significant difference (Sig. 0.006 < 0.05). The psychomotor aspect showed the most substantial gain, with a significance value of 0.000, confirming the effectiveness of PjBL in developing students' skills. Additionally, regression analysis demonstrated that learning motivation significantly influences learning outcomes (Sig. 0.044). This research contributes empirical evidence that Project-Based Learning effectively enhances both motivation and learning outcomes in elementary education, supporting the implementation of Merdeka Curriculum's deep learning approach and reinforcing constructivist principles of active, experience-based learning.